Volatility as a Legal Challenge: Rethinking Labor Law Responses to Workplace Violence - European Approach - Kobroń-Gąsiorowska, Łucja (Review of European and Comparative Law, 2026)
Workplace violence is a growing concern in contemporary labor law, driven by its prevalence and volatile nature. Effective legal analysis requires understanding volatility as the variability, unpredictability, repetition, and context-dependence of violent and abusive conduct. Workplace violence is not isolated or uniform but is shaped by changing social, economic, organizational, and regulatory factors. Its forms, intensity, frequency, and visibility shift over time, across sectors, and among different groups, especially regarding gender and socio-economic status. This volatility exposes the limitations of uniform regulatory models that assume stable risks. Evidence from Europe and Central Asia shows that violence and harassment are often recurrent, disproportionately affect women, and persist despite strong legal frameworks. The frequent occurrence of psychological and sexual harassment, along with underreporting in precarious or low-income settings, highlights gaps between formal legal protections and their practical effectiveness. Volatility impacts of only the occurrence of violence but also access to remedies, reporting, enforcement, and employer compliance. The protective function of labor law depends on its ability to address these volatile patterns. Volatility challenges complaint-based models and underscores the need for preventive, ongoing, and context-sensitive legal duties. This includes gender-sensitive risk assessments, differentiated employer obligations, and recognition of repeated violence as an aggravated violation, as well as greater attention to psychosocial harm. By viewing workplace violence as an evolving risk, the author advocates for a new approach to labor regulation in Europe that prioritizes substantive equality, early intervention, and effective enforcement over formally neutral but insufficient standards.